Bioengineered Nanozymes for Orthopedic Degenerative Diseases: From Catalytic Mechanisms to Multimodal Therapy - Lei Peng; Chen Yan; Honghao Song; Jiangang Shi; Kaiqiang Sun (MedComm – Biomaterials and Applications)
ABSTRACT Orthopedic degenerative diseases, particularly osteoarthritis (OA) and intervertebral disc degeneration (IDD), represent a growing global health crisis. Current clinical management relying on analgesics and anti‐inflammatory drugs provides only symptomatic relief, while surgical interventions, though temporarily effective for advanced cases, carry inherent risks of adjacent segment degeneration and surgical complications. Synthetic nanozymes, which possess intrinsic anti‐inflammatory and antioxidant properties, demonstrate significant therapeutic advantages in the treatment of orthopedic degenerative diseases. This review summarizes recent advances in nanonzyme‐based therapeutics, with a focus on their regulatory roles in mitigating orthopedic degenerative diseases, particularly IDD and OA. Key mechanisms include anti‐inflammatory effects, extracellular matrix remodeling, attenuation of cellular senescence and death, and antioxidative stress activities. We systematically analyze nanonzymes categorized by their diverse enzymatic activities and chemical compositions. Furthermore, we explore emerging combinatorial strategies employing nanonzyme delivery systems to achieve synergistic therapeutic outcomes and enhanced efficacy. The comprehensive discussion highlights the transformative potential of nanonzymes in advancing IDD and OA treatment paradigms, offering novel perspectives for future research and clinical applications.